Assisting in the planning for the establishment of an Arabic Language Education study program based on the outcome-based education curriculum at STAI Mempawah - Rahmap, Rahmap; Widiatmaka, Pipit; Syahni, Sy. Muhammad Riza; Khairunnisa, Khairunnisa (Community Empowerment, 2025)
Recognizing the crucial need for developing relevant curricula in higher education, this community service activity aimed to facilitate the planning of an Arabic Language Education study program adopting an Outcome-Based Education (OBE) curriculum at Sekolah Tinggi Agama Islam (STAI) Mempawah. Utilizing a participatory action research (PAR) approach through Focus Group Discussions (FGDs) and workshops, this assistance successfully enhanced partners' knowledge about the concept and implementation of the OBE curriculum. Furthermore, it garnered a strong commitment from STAI leadership, supported by the government and stakeholders, to establish the program by 2025. This initiative represents a strategic step in improving the quality of Islamic higher education, particularly in West Kalimantan.